Kreativitas dan Keaktifan Pembelajaran Kimia Melalui Project Based Learning Berbantuan Podcast Pada Materi Larutan Penyangga - Ayukinah - Ayukinah (Chemistry Education Department of Education and Teaching Faculty, 2022)
This classroom action research was conducted with the aim of finding a solution to the problem of low creativity and activeness of students in class XI IPA. The treatment applied to the research is project-based learning assisted by podcasts. The research consisted of two cycles, namely cycle I and cycle II. The data in the classroom action research consisted of qualitative data from observations and quantitative data in the form of processing scores of students' creativity and activeness. The results showed that there was a significant increase in the creativity and activeness of students after the actions of cycle I and cycle II. Research performance indicators were achieved in cycle II. The average score for each creativity indicator tested was in the very good category, with a score range of 90.89-93.11. The activity of class XI IPA students increased by 93.27% in cycle II. This shows that the hypothesis is accepted (the treatment can increase the creativity and activeness of students).The application of the project-based learning model assisted by podcasts is effective and can be used as a solution to the problem of low creativity and activeness of students in chemistry subjects. Furthermore, the use of combined innovation between learning models and learning media can be used as a solution that will facilitate students' ability to improve the various skills they have